Bacterial-fungal metabolic interactions within the microbiota and their potential relevance in human health and disease: a short review - Alexia Lapiere; Mathias L Richard (Gut Microbes)
The composition of the microbiota is the focus of many recent publications describing the effects of the microbiota on host health. In recent years, research has progressed further, investigating not only the diversity of genes and functions but also metabolites produced by microorganisms composing the microbiota of various niches and how these metabolites affect and shape the microbial community. While an abundance of data has been published on bacterial interactions, much less data are available on the interactions of bacteria with another component of the microbiota: the fungal community. Although present in smaller numbers, fungi are essential to the balance of this complex microbial ecosystem. Both bacterial and fungal communities produce metabolites that influence their own population but also that of the other. However, to date, interkingdom interactions occurring through metabolites produced by bacteria and fungi have rarely been described. In this review, we describe the major metabolites produced by both kingdoms and discuss how they influence each other, by what mechanisms and with what consequences for the host.